Will doctor rating sites improve standards of care? Yes. (17th March 2009) - Bacon, Neil
Abstract : The UK government has signalled its support for rating sites with the decision to set up its own through the NHS Choices website. Neil Bacon believes they provide essential feedback for doctors, but Margaret McCartney ( doi:10.1136/bmj.b1033 ) is concerned that the potential harms are still unclear